Yarrowia lipolytica N6-glucan protects goat leukocytes against Escherichia coli by enhancing phagocytosis and immune signaling pathway genes. (January 2021) - Angulo, Miriam; Reyes-Becerril, Martha; Angulo, Carlos
Abstract: Immunostimulant and protective effects of Yarrowia lipolytica glucans against important pathogens, such as Escherichia coli, have not been investigated in goats and other ruminants. This study aimed to characterize Y. lipolytica N6-glucan ( Yl -glucan) and its possible role in immunological signaling pathway activation and immunoprotection against E. coli in goat leukocytes. Characterization analyses showed that Y. lipolytica content had a mix of β and α-D-glucans, molecular weight of 3301.53 kDa and low solubility after the heat treatment. The stimulation of goat leukocytes with Yl -glucan induced protection against E. coli challenge. Remarkably, Yl- glucan and E. coli interaction increased gene expression of dectin-1 and TLR-2 receptors, signaling pathway Syk/NFκB, and cytokines, such as TNF-α and IL-10. As a consequence of signaling activation, phagocytosis, and nitric oxide production enhanced killing of pathogens. Altogether, Y. lipolytica- glucan demonstrated to possess an immunoprotective potential against E. coli through innate immune response modulation in goat leukocytes. Highlights: Glucan from marine yeast Yarrowia lipolytica ( Yl -glucan) was characterized. NMR indicated structures of a mix of β and α-D-glucans with low molecular weight. Yl -glucan was not cytotoxic for goat peripheral blood leukocytes (GPBL). Yl -glucan enhanced immune parameters and protected PBL viability against Escherichia coli challenge. Yl -glucan and E. coli interaction upregulated Dectin-1 and TLR-2/Syk/NFκB/TNF-α and IL-10 signaling pathways genes.